Relationship of brain derived neurotrophic factor (BDNF) DNA methylation with schizophrenia - Abd. Rahim, Nour El Huda; Rahim, Mohd Nabil Fikri; Ku Zaifah, Norsidah; Mohd Noor, Hanisah; Abdullah, Kartini; A.Talib, Norlelawati (2016)
Epigenetic is a mutual interaction between the gene and environment. It forms the basis of many diseases including Schizophrenia. Brain derived neurotrophic factors (BDNF) contributes to neurodeveloment hypothesis of Schizophrenia since its function is to facilitate neuronal signaling and survival. Hypermethylated effect of BDNF gene may cause reduction in BDNF transcription. Thus, contribute to pathophysiology of Schizophrenia. The objective of this study is to assess the relationship of BDNF gene DNA methylation in Schizophrenia. A total of 240 participants (118 Schizophrenia and 122 healthy controls) were recruited. Genomic DNA was extracted from peripheral blood and bisulfite treated. The Methylight Taqman analysis method was adopted for the quantitation of the methylation level. Sociodemographic variables were gathered through interview and the review of the medical records. There was no significant difference of DNA methylation between the two study groups. However, among males, the DNA methylation level of BDNF was significantly increased as compared to the healthy control (p = 0.016). Further analysis among Schizophrenia showed significant inverse correlation between the level of methylation and age of the patients (r=-0.089, p=0.001) and the number of years of having the disease (r=-0.120, p=0.000). Otherwise, there were no correlation between BDNF DNA methylation level with body mass index, age of diagnosis, educational status and smoking status. Methylation status is related to Schizophrenia among males. However this sex specific tendency may require further evaluation. The reduction of methylation status with aging and duration of illness follows the typical degradation of methylation observed in aging.